Preparation of Polyacrylamide Titanium Dioxide Hybrid Nanocomposite by Direct Polymerization and Its Applicability in Removing Crystal Violet From Aqueous Solution - Arslan, Dilek Senol; Ertap, Hueseyin; Senol, Zeynep Mine; El Messaoudi, Noureddine; Mehmeti, Valbone (Springer, 2023)
The present paper focused on synthesizing a polyacrylamide-titanium dioxide (PAA@TiO2) nanocomposite using a cross-linking method with N, N & PRIME;-methylenebisacrylamide and then using this composite to eliminate crystal violet (CV) dye from water and to characterize the adsorbent by XRD, FT-IR, and SEM-EDX techniques. The characterization revealed that TiO2 nanoparticles dispersed homogeneously within the polymer matrix. The maximum amount of adsorption was about 38.9 mg g(-1) under the adsorbent dose of 5 g L-1, 500 mg L-1 CV dye concentration, and pH 6.9. The interaction between the CV molecule and the PAA@TiO2 nanocomposite surface was studied using Monte Carlo (MC) and molecular dynamics (MD) simulations. The negative value of the Eads (- 586.56 kcal mol(-1)) of the CV molecules onto the PAA@TiO2 nanocomposite surface gives credibility to the experimental results. All obtained results showed that PAA@TiO2 hybrid polymer nanocomposite could be an alternative adsorbent for crystal violet dye removal from wastewater.
Noureddine, El Messaoudi/0000-0003-2762-1395;
Keywords: Polyacrylamide; Tio2 Nanoparticles; Nanocomposite; Dye; Adsorption; Wastewater Treatment; TiO2 Nanoparticles